Potential differentiation of three types of primitive cells originated from different proliferation terms of mouse blood - Intan Zarina Zainol Abidin; Shahrul Hisham Zainal Ariffin; Zaidah Zainal Ariffin; Rohaya Megat Abdul Wahab (Universiti Kebangsaan Malaysia, 2010)
The aim of this study was to differentiate central blood system mononucleated cells in vitro into osteoblast and osteoclast cells for three different proliferation terms of cells. The mononucleated cells were cultured in a selective proliferation medium for three different proliferation terms, i.e., short (5 days), medium (15 days) and long term (30 days) prior to analysis of osteoblast and osteoclast cells’ differentiation potentialities. The proliferation medium was then supplemented with differentiation factors, i.e., ascorbic acid and β-glycerophosphate to differentiate mononucleated cells into osteoblast cells. For osteoclast assay, RANKL and M-CSF were added into proliferation medium. For control, the same cells were used without supplementation of respective differentiation factors. The viability of differentiated cells from short, medium and long types of cells showed that they were able to survive until 10 to 14 days in the presence of respective differentiation factors without significant increased in the specific differentiation medium. Biochemical analyses on both alkaline phosphatase (ALP) and tartrate resistant acid phosphatase (TRAP) activities were significantly increased (p<0.05) once cultured in their respective differentiation medium. In conclusion, the three types of primitive cells have the same potentiality to differentiate into mature osteoblast and osteoclast cells even though the proliferation rates are different, i.e. 0.37, 0.55 and 0.72 division/day for short, medium and long term cells respectively. Mononucleated cells isolated from peripheral blood are primitive enough to differentiate into two distinct types of mature cells which originated from two different stem cells lineage hence can be categorized as multipotent stem cells.